2007
DOI: 10.1038/sj.npp.1301578
|View full text |Cite
|
Sign up to set email alerts
|

Acute Physiological and Behavioral Effects of Intranasal Methamphetamine in Humans

Abstract: Intranasal methamphetamine abuse has increased dramatically in the past decade, yet only one published study has investigated its acute effects under controlled laboratory conditions. Thus, the current study examined the effects of single-dose intranasal methamphetamine administration on a broad range of behavioral and physiological measures. Eleven nontreatment-seeking methamphetamine abusers (two females, nine males) completed this four-session, in-patient, within-participant, double-blind study. During each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
98
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(109 citation statements)
references
References 35 publications
11
98
0
Order By: Relevance
“…Methamphetamine administered alone dose dependently increased positive subject-rated drug-effects (e.g., Like Drug; Willing to Take Again), which is consistent with the results of previous research (e.g., [21][22][23][24]. d-Amphetamine maintenance attenuated some of the positive subject-rated drug-effects, which is consistent with a previous study that showed 45 mg/day d-amphetamine reduced the subject-rated drug-effects of methamphetamine (8).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Methamphetamine administered alone dose dependently increased positive subject-rated drug-effects (e.g., Like Drug; Willing to Take Again), which is consistent with the results of previous research (e.g., [21][22][23][24]. d-Amphetamine maintenance attenuated some of the positive subject-rated drug-effects, which is consistent with a previous study that showed 45 mg/day d-amphetamine reduced the subject-rated drug-effects of methamphetamine (8).…”
Section: Discussionsupporting
confidence: 82%
“…Finally, methamphetamine dose dependently increased systolic blood pressure and d-amphetamine maintenance attenuated these increases, compared to placebo maintenance. These findings are consistent with the results of prior studies that showed intranasal methamphetamine is safe and well-tolerated in a controlled laboratory setting (8,16,17,(22)(23)(24) and that d-amphetamine maintenance reduces some of the cardiovascular effects of methamphetamine (8). The attenuation of cardiovascular effects of methamphetamine during d-amphetamine maintenance may be attributable to participants developing cross-tolerance to the cardiovascular effects of stimulants.…”
Section: Discussionsupporting
confidence: 82%
“…Medication also moderated ratings of 'bad drug effects' following MA administration, such that ratings of 'bad drug effects' were higher on NTX than placebo at earlier time points following MA infusion. NTX did not significantly alter peak MA effects; however, although peak drug responses are important factors in stimulant abuse (Hart et al, 2008), the modulation of broader acute subjective effects, such as those observed in this study, represent equally important targets for pharmacological intervention. As would be predicted, there were elevations in heart rate and blood pressure in response to the MA cues and to the MA administration.…”
Section: Discussionmentioning
confidence: 83%
“…However, this study did not administer urinalyses to ensure that participants were drug free at the time of testing, which is important considering that acute MA can improve baseline performance (Hart et al, 2008;Mahoney et al, 2011). Further, it is unclear whether the weekly use of MA examined in this study constitutes either dependence or abuse as defined by the DSM-IV.…”
Section: Resultsmentioning
confidence: 99%